Color-detection thresholds in rhesus macaque monkeys and humans - Gagin, Galina (J Vis, 2014)
Macaque monkeys are a model of human color vision. To facilitate linking physiology in monkeys with psychophysics in humans, we directly compared color-detection thresholds in humans and rhesus monkeys. Colors were defined by an equiluminant plane of cone-opponent color space. All subjects were tested on an identical apparatus with a four-alternative forced-choice task. Targets were 2° square, centered 2° from fixation, embedded in luminance noise. Across all subjects, the change in detection thresholds from initial testing to plateau performance (“learning”) was similar for +L − M (red) colors and +M − L (bluish-green) colors. But the extent of learning was higher for +S (lavender) than for −S (yellow-lime); moreover, at plateau performance, the cone contrast at the detection threshold was higher for +S than for −S. These asymmetries may reflect differences in retinal circuitry for S-ON and S-OFF. At plateau performance, the two species also had similar detection thresholds for all colors, although monkeys had shorter reaction times than humans and slightly lower thresholds for colors that modulated L/M cones. We discuss whether these observations, together with previous work showing that monkeys have lower spatial acuity than humans, could be accounted for by selective pressures driving higher chromatic sensitivity at the cost of spatial acuity amongst monkeys, specifically for the more recently evolved L − M mechanism.